As aventuras de Lázaro nas terras do sem fim: o ler no ciberespaço - Viana, Helem Alves (2012)
Storms to human thought produced by the magic of Gutenberg cause, especially in our days, fascinating questions about the fate of writing, books and media in which we keep our ideas and memories. This study investigates the experience of reading and textual production nowadays. It discusses literature, the book and its transformations in the face of new technologies, bringing the experience of creation of the digital multimedia book Lazarus in the land of endlessness, done on the iPad, inspired by the works Memories Lazarus by Adonias Filho and The violent Land of Jorge Amado - as well as the concept of Commonplace book. Based on the Six Memos for the Next Millennium by Italo Calvino and on the thoughts of Katherine Hayles and Sergio Basbaum, sets up a dialogue about literature today; the analogic book and digital book are discussed from theoreticians as George Steiner, Vilem Flusser, Marshall McLuhan and Robert Darnton, paying special attention to literary criticism. Finally, given the wealth of technological innovations, the ubiquity of digital mediation and the possibilities opened by this revolution, the dissertation ends with the evolution and refinement of the original question, regarding the use of new technologies in the teaching of literature, since the contemporary context does not allow conclusive determinations, emphasizing the importance of Internet access and to new technological tools - given the possibilities for the future of the book and the place of reading in the twenty-first century